Praksis, praktisk filosofi, praksisfilosofi og pragmatisme - bidrag til begrebsafklaring - Fink, Hans (Slagmark - Tidsskrift for idéhistorie, 2018)
It is common to distinguish between theoretical and practical philosophy and also between pure philosophy and philosophy applied to or engaged with some form of practice. Quite different conceptions of practice and the practical are, however, underlying these distinctions. In this paper both distinctions are traced back to Aristotle’s complicated understanding of praxis. An Aristotelian-Kantian tradition allows a conception of practical philosophy which is explicitly avoided within an Aristotelian-Hegelian tradition. Pragmatism belongs to the latter tradition along with modern forms of philosophy of practice or philosophy in practice. The paper attempts to give an overview of the many different uses of the concept of practice in modern philosophy and tentatively recommends a pragmatist approach.